A randomized controlled trial comparing functional outcomes for navigated kinematically aligned total knee arthroplasty versus navigated mechanically aligned total knee arthroplasty THE MAKKRO TRIAL. (2021) - Sadekar, V. N.; Datir, S.; Allgar, V.; Sharma, H.
No abstract available